Targeting oxidative phosphorylation as an approach for the treatment of ovarian cancer - Wu, Yinjie; Zhang, Xuewei; Wang, Ziyi; Zheng, Wanzhen; Cao, Huimin; Shen, Wenjing (Frontiers in Oncology, 2022)
Ovarian cancer is an aggressive tumor that remains to be the most lethal gynecological malignancy in women. Metabolic adaptation is an emerging hallmark of tumors. It is important to exploit metabolic vulnerabilities of tumors as promising strategies to develop more effective anti-tumor regimens. Tumor cells reprogram the metabolic pathways to meet the bioenergetic, biosynthetic, and mitigate oxidative stress required for tumor cell proliferation and survival. Mitochondrial oxidative phosphorylation has been found to be altered in ovarian cancer, and oxidative phosphorylation is proposed as a therapeutic target for management of ovarian cancer. Herein, we initially introduced the overview of oxidative phosphorylation in cancer. Furthermore, we discussed the role of oxidative phosphorylation and chemotherapeutic resistance of ovarian cancer. The role of oxidative phosphorylation in other components of tumor microenvironment of ovarian cancer has also been discussed.